2021
DOI: 10.2196/17116
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Profiles of eHealth Users Evaluated Using Data Mining Techniques: Cohort Study

Abstract: Background New technologies are changing access to medical records and the relationship between physicians and patients. Professionals can now use e-mental health tools to provide prompt and personalized responses to patients with mental illness. However, there is a lack of knowledge about the digital phenotypes of patients who use e-mental health apps. Objective This study aimed to reveal the profiles of users of a mental health app through machine lea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…In contrast to our findings, none of the abovementioned studies found a difference in gender use. However, a more recent Spanish study found that women used the modules more than men [27]. In accordance with our findings, the Spanish study also found that the modules for mood disorders were highest in use among the other modules [27].…”
Section: Comparison With Prior Worksupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast to our findings, none of the abovementioned studies found a difference in gender use. However, a more recent Spanish study found that women used the modules more than men [27]. In accordance with our findings, the Spanish study also found that the modules for mood disorders were highest in use among the other modules [27].…”
Section: Comparison With Prior Worksupporting
confidence: 91%
“…The website [11] was launched on August 1, 2015, prior to the population survey in Nickerie (which was held from August [15][16][17][18][19][20][21][22][23][24][25][26][27]2015). Interest was generated in this period during the informative sessions with the doctors, district commissioners, police officers, and civil servants that helped during the survey.…”
Section: Procedures and Data Collectionmentioning
confidence: 99%
“…Various previous research using data mining was carry doubt to deal with mental health [3,4,5]. Due to change in behavior the symptoms change in mental disorder and so it needs intelligent mechanism to classify it [6,7].…”
Section: Introductionmentioning
confidence: 99%